Elevated Osteopontin Levels in Mild Cognitive Impairment and Alzheimer’s Disease - Yuan Sun; Xue Song Yin; Hong Guo; Rong Kun Han; Rui Dong He; Li Jun Chi (Mediators of Inflammation)
Inflammatory mediators are closely associated with the pathogenesis of neurodegenerative changes in Alzheimer’s disease (AD) and mild cognitive impairment (MCI). Osteopontin (OPN) is a proinflammatory cytokine that has been shown to play an important role in various neuroinflammatory diseases. However, the function of OPN in AD and MCI progression is not well defined. Cerebrospinal fluid (CSF) and plasma samples were obtained from 35 AD patients, 31 MCI patients, and 20 other noninflammatory neurologic diseases (OND). Concentrations of OPN in the CSF and plasma were determined by enzyme-linked immunosorbent assay. During a 3-year clinical followup, 13 MCI patients converted to AD (MCI converters), and 18 were clinically stable (MCI nonconverters). CSF OPN concentrations were significantly increased in AD and MCI converters compared to OND, and increased levels of OPN in AD were associated with MMSE score; OPN protein levels both in the CSF and plasma of newly diagnosed AD patients were higher than that of chronical patients. In MCI converters individuals tested longitudinally, both plasma and CSF OPN concentrations were significantly elevated when they received a diagnosis of AD during followup. Further wide-scale studies are necessary to confirm these results and to shed light on the etiopathogenic role of osteopontin in AD.